Effect of Rewarming on Leukocyte-Endothelial Interaction After Deep Hypothermic Preservation - Bogert, Nicolai V. (Ann Transplant, 2020)
BACKGROUND: The preservation of harvested organs plays an essential role in transplantation. Cold hypothermia is frequently applied but may lead to graft compromise resulting from reperfusion and rewarming injury. This study investigates the effect of deep hypothermia and posterior rewarming on leukocyte-endothelial interactions and junctional adhesion molecules. MATERIAL/METHODS: We established an in vitro model to investigate the transendothelial migration of leukocytes (TEM) during deep hypothermia (4°C) as well as during the post-hypothermic rewarming process. Additionally, leukocyte-endothelial interactions were analyzed by quantifying surface expression of the junctional adhesion molecules A (JAMA-A and JAM-B). RESULTS: While deep hypothermia at 4°C was associated with reduced leukocyte infiltration, rewarming after hypothermic preservation resulted in a significant increase in TEM. This process is mainly triggered by activation of endothelial cells. Post-hypothermic rewarming caused a significant downregulation of JAM-A, whereas JAM-B was not altered through temperature modulation. CONCLUSIONS: Hypothermia exerts a protective effect consisting of reduced leukocyte-endothelial interaction. Rewarming after hypothermic preservation, however, causes considerable upregulation of leukocyte infiltration. Downregulation of JAM-A may play a role in modulating TEM during hypothermia and rewarming. We conclude that the rewarming process is an essential but underestimated aspect during transplantation.